KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 4 KAMBOWA - Wa Ode Bella Silfara Bella; Wa ode Fitriani Sari; Asmawati (Jurnal Bastra (Bahasa dan Sastra), 2025)
The problem in this study is how is the ability to write description texts for grade VII students of SMP Negeri 4 Kambowa? The purpose of this study is to describe the ability to write description texts of grade VII students of SMP Negeri 4 Kambowa. The type of research used in this study is field research, and the method used in this study is quantitative descriptive. The sampling technique in this study uses a total sampling technique, the sample is taken as much as the total population so that it involves all students in grade VII of SMP Negeri 4 Kambowa totaling 29 students. The instrument used in this study is a writing test, which is the ability to write descriptive texts based on the structure of descriptive texts and the use of language. Based on the results of the study, of the 29 students who participated in the study, 34, 48% were classified as capable and there were 65, 51% classified as indigent, here are the details of the percentage of completion criteria; (a) Students who have acquired excellent skills in writing descriptive texts amounted to 2 students or 6.89% (b) Students who acquired good skills in writing descriptive texts amounted to 5 students or 17.24% (c) Students who acquired sufficient ability in writing descriptive texts amounted to 3 students or 10.34% (d) Students who acquired the ability to need guidance in writing descriptive texts amounted to 19 students or 65, 51%.